2022
DOI: 10.1002/cam4.5413
|View full text |Cite
|
Sign up to set email alerts
|

The effect of EGFR‐TKIs on survival in advanced non‐small‐cell lung cancer with EGFR mutations: A real‐world study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…25 Yu, et al (2023) also reported different results where the median OS in exon 19 del mutations was better than exon 21 L858R with a very significant difference (mOS 32.4 vs. 24.83, p = 0.0013). 26 As previously explained, the OS and PFS curves based on the EGFR common mutation type intersect, meaning there was no significant relationship between both types. The Proportional Hazard assumption was not met, meaning that the survival rate and PFS ratio between the two types of mutations were not constant.…”
Section: Discussionmentioning
confidence: 87%
“…25 Yu, et al (2023) also reported different results where the median OS in exon 19 del mutations was better than exon 21 L858R with a very significant difference (mOS 32.4 vs. 24.83, p = 0.0013). 26 As previously explained, the OS and PFS curves based on the EGFR common mutation type intersect, meaning there was no significant relationship between both types. The Proportional Hazard assumption was not met, meaning that the survival rate and PFS ratio between the two types of mutations were not constant.…”
Section: Discussionmentioning
confidence: 87%
“…These findings are consistent with similar studies which reported longer overall survival in subjects with EGFR Exon 20 T790M mutations who received EGFR-TKI treatment compared to those without the mutation and without EGFR-TKI treatment. (27) There are some limitations of the current study. To overcome these limitations and gain a deeper understanding of the clinical outcomes and prognosis associated with the EGFR Exon 20 T790M, a multi-center study with a larger sample size is recommended.…”
Section: Discussionmentioning
confidence: 88%
“…Systemic treatment for stage IV NSCLC has entered the era of precision therapy, including chemotherapy, 8 targeted therapy, 9 and immunotherapy 10,11 . Tyrosine kinase inhibitors (TKIs) can achieve an excellent therapeutic response in NSCLC with positive mutations in driver Genes and significantly improve progression‐free survival (PFS) 12–15 .…”
Section: Introductionmentioning
confidence: 99%